UJI DAYA HAMBAT EKSTRAK ETANOL BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP BAKTERI Staphylococcus aureus DALAM SEDIAN GEL - wirayustika, wirayustika (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the inhibitory power of ethanol extract of rosella flowers (Hibiscus sabdariffa L.) against Staphylococcus aureus bacteria in gel preparations. The type of this research was to test the inhibitory power of ethanol extract obtained from rosella flowers (Hibiscus sabdariffa L.) against Staphylococcus aureus bacteria in gel preparation. The sample is rosella flower extract (Hibiscus sabdariffa L.) obtained from Daya, Paccerakkang Makassar. The tools used in this research were an autoclave (Smi model YX 280-B), a maceration tool, a petri dish, a porcelain dish, a glass beaker, an Enlenmeyer glass (Iwaky Pyreks), an incubator (Memmert), a magnetic stirrer, an O'hauss balance, an oven. (memmert), circular tubes, water heaters, analytical and vital scales. The materials used were 96% ethanol, agar, distilled water, pure culture of (Staphylococcus aureus) rosella flowers, 0.9% NaCl physiological solution, Medium Nutrient Agar (NA), samples of rosella flowers (Hibiscus Sabdariffa L.) distilled water. The sample used was rosella flowers (Hibiscus Sabdariffa L.) obtained in Daya, Paccerakkang Makassar. Based on the results of research and discussion, it can be concluded that ethanol extract of rosella flowers (Hibiscus sabdariffa L.) in gel dosage form can inhibit the growth of Staphylococcus aureus bacteria at concentrations of 1%, 3%, 5%.